High-risk human papillomavirus in non-melanoma skin lesions from renal allograft recipients and immunocompetent patients - Reuschenbach, Miriam; Tran, Thuong Hien; Faulstich, F.; Hartschuh, Wolfgang; Vinokurova, S.; Kloor, Matthias; Krautkrämer, E.; Zeier, Martin; Knebel Doeberitz, Magnus von; Sommerer, Claudia (British journal of cancer, 2011)
Background: High-risk human papillomaviruses (HR-HPVs) can be detected in a proportion of non-melanoma skin cancers. Data on prevalence are inconclusive, but are essential to estimate the relevance of HR-HPV, particularly with regard to prophylactic HPV vaccines for skin cancer prevention. Methods: High-risk human papillomavirus DNA was investigated in 140 non-melanoma skin lesions from 54 immunocompetent patients and 33 immunosuppressed renal allograft recipients. Expression of p16INK4a, a marker for HR-HPV oncogene expression in the uterine cervix, and of p53 and pRB was evaluated immunohistochemically. Results: The highest prevalence of HR-HPV was found in squamous cell cancer (SCC) (46.2% (6 out of 13) in immunosuppressed and 23.5% (4 out of 17) in immunocompetent patients). High-risk human papillomavirus positivity was accompanied by diffuse p16INK4a expression in most SCC (P<0.001) and basal cell cancers (P=0.02), while almost all SCC in situ were p16INK4a positive irrespective of HR-HPV presence (P=0.66). Diffuse p16INK4a expression was associated with lack of pRB expression (P=0.001). p53 was strongly expressed in 40.0% (56 out of 140) of the lesions irrespective of HR-HPV presence. Conclusion: High-risk human papillomavirus can be detected in lesions of keratinised squamous epithelia. The association of HR-HPV with diffuse p16INK4a expression might indicate HR-HPV oncogene expression in a proportion of lesions. Overexpression of p53 suggests p53 pathway alterations in HR-HPV-positive and -negative lesions.
Gesehen am 15.09.2022